DEVELOPMENT OF A SIMULATION SOFTWARE FOR MACHINE ADDITION PLANNING IN A JOB-SHOP ENVIRONMENT - Zainal Arif (NIM : 13500010), Endang
Abstract: Simulation is an approach to predicting some result by imitating the real system. The imitation, known as model, is then executed in a computer. The result we obtain from a simulation is just an estimation. Simulation with a good model that is representative enough to the real system, however, will give us a good estimation. In this final project, simulation will be applied to a resources (machines) planning in a typical manufacture environment, known as job-shop environment. In a job-shop environment there are some stations that serve the task of each job that come to them. The more jobs come to a station, the higher 3 measures related to that station will be. The 3 measures are average number of jobs waiting to be served by the machine (average number), average utilization of a machine (average utilization), and average delay of jobs queuing in that machine (average delay). The station with the highest value of this measure will need additional machine the worst. By a simulation execution, the location of a machine with the highest measure can predicted. The result of this final project is a software application that uses the above idea to make a machines addition planning. The plan adds to each station some new machines, so that the new machine configuration is expected to be the most optimal. The optimal system is the one with the overall system delays reduced the most. At the end of this final project, it can be concluded that the configuration of a new job-shop machine obtained by simulation using one of the 3 measures will give a more optimal system than the one obtained using a straight forward way, in which new machines is added with an equal number to every stations.